Penerapan Asas Legalitas Dalam Tindak Pidana Pencucian Uang Oleh Korporasi Dalam Pemberantasan Tindak Pidana Korupsi Di Indonesia Ditinjau Dari Undang-Undang Nomor 20 tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi Dan Undang-Undang Nomor 8 Tahun 2 - Ressa Januarti Munggaran (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2025)
The crime of money laundering as an international crime has a negative impact on a country's economy. This crime of money laundering can be committed not only by individuals, but also by companies. When it comes to the existence of companies as subjects of criminal law that can be subject to criminal responsibility, questions arise regarding when a company is declared a perpetrator of money laundering and what criteria indicate that the company has committed the crime of money laundering. The analysis of the results of this study shows that: (I) Based on the definition of money laundering contained in Black's Law Dictionary, in general the elements of the crime of money laundering include the existence of money (funds) that are the result of illegal activities, illicit money or dirty money that is processed in a certain way through a legal or legitimate institution, with the aim of eliminating traces, so that the source of the money cannot or is difficult to know and trace. A company can be considered to have committed the crime of money laundering if it meets the elements of the crime contained in Law No. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering, (II) The form of corporate responsibility is regulated in Articles 3 to 10 of Law No. 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes. Companies can be subject to legal sanctions with a principal penalty in the form of a fine and may be subject to additional penalties. If the criminal fine cannot be paid, the fine can be replaced by the confiscation of assets owned by the company or the company's controlling personnel, and if the confiscation of assets is still insufficient, then the company that commits the crime of money laundering can be sentenced to imprisonment in lieu of a fine against the company's controlling personnel with a maximum prison sentence of 1 (one) year and 4 (four) months.